CPWF Volta V2 Main Message Poster - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2013)
Innovation platforms provide spaces for a wide range of stakeholders to exchange knowledge, learn, and develop joint initiatives to solve agricultural development challenges. Successful innovation can only happen when stakeholders have a sustained interest in working together to acquire new knowledge and find solutions; the research community cannot bring about innovation on its own.